2016
DOI: 10.15585/mmwr.mm6533a4
|View full text |Cite
|
Sign up to set email alerts
|

National, Regional, State, and Selected Local Area Vaccination Coverage Among Adolescents Aged 13–17 Years — United States, 2015

Abstract: Local areas that received Federal Section 317 immunization funds were sampled separately: Chicago, Illinois; New York, New York; Philadelphia County, Pennsylvania; Bexar County, Texas; and Houston, Texas. Two local areas (in Texas) were oversampled: El Paso County and Hidalgo County. Three territories was sampled separately in 2015: Guam, Puerto Rico, and the U.S. Virgin Islands. ¶ All identified cellular telephone households were eligible for interview. Sampling weights were adjusted for dual-frame (landline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
333
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(346 citation statements)
references
References 8 publications
(7 reference statements)
9
333
4
Order By: Relevance
“…Although several studies have shown that HPV vaccination does not affect subsequent sexual behavior (Liddon, Leichliter, & Markowitz, 2012) and that overall HPV vaccination is both safe and effective in reducing HPV prevalence (Markowitz et al, 2013), vaccination rates remain low across adolescents in the United States, with only 39.7% of girls and 21.6% of boys aged 13 to 17 estimated to have completed the series in 2014 (Reagan-Steiner et al, 2015). Although there was a slight increase in the overall vaccination completion rate in females from the previous year, the rate of uptake for HPV vaccination continues to lag behind other adolescent vaccines, resulting in a pressing need to identify effective ways of increasing uptake across different populations (Ferrer, Trotter, Hickman, & Audrey, 2014;Fu, Bonhomme, Cooper, Joseph, & Zimet, 2014;Mayne et al, 2012;Perkins et al, 2015).…”
Section: Articlementioning
confidence: 99%
“…Although several studies have shown that HPV vaccination does not affect subsequent sexual behavior (Liddon, Leichliter, & Markowitz, 2012) and that overall HPV vaccination is both safe and effective in reducing HPV prevalence (Markowitz et al, 2013), vaccination rates remain low across adolescents in the United States, with only 39.7% of girls and 21.6% of boys aged 13 to 17 estimated to have completed the series in 2014 (Reagan-Steiner et al, 2015). Although there was a slight increase in the overall vaccination completion rate in females from the previous year, the rate of uptake for HPV vaccination continues to lag behind other adolescent vaccines, resulting in a pressing need to identify effective ways of increasing uptake across different populations (Ferrer, Trotter, Hickman, & Audrey, 2014;Fu, Bonhomme, Cooper, Joseph, & Zimet, 2014;Mayne et al, 2012;Perkins et al, 2015).…”
Section: Articlementioning
confidence: 99%
“…1 In the extensive research literature that seeks to explain low HPV vaccination coverage, many studies have focused on parents of adolescents because they are most often responsible for making HPV vaccination decisions. 2 These studies, including our own, have typically examined the relationship between parents' vaccination beliefs, their intention to vaccinate their adolescents, and adolescents' ultimate vaccination status.…”
mentioning
confidence: 99%
“…Another important concern is that only 2 in 5 girls and 1 in 5 boys aged 13-17 years in the US have received the recommended full series (three doses) of the vaccine (Reagan-Steiner et al, 2015). Low uptake is regarded as the primary obstacle to attaining the goal of reducing morbidity and mortality associated with HPV infection.…”
mentioning
confidence: 99%